Microvasculature of Anterior Cruciate Ligament by Immunohistochemistry using VE-Cadherin - Jahira Banu T; Yogesh Ashok Sontakke (Academia Anatomica International, 2020)
Introduction: The anterior cruciate ligament (ACL) is one of the knee stabilizer and acts to prevent excessive anterior mobility as well as rotational movement. The ACL is extending from the lateral femoral condyle to the anterior intercondylar area of tibia. During excessive movement or abnormal mobility affecting the knee joint, the ACL is under tension and prone for injury. The injured ACL was managed by surgery as it was an option for treatment owing to its poor vascularity. The distribution of the blood vessels within the ACL was not clear and only few studies reported in the past. The present study focused on distribution of blood vessels in the ACL. Subjects and Methods: The ACL microvasculature was assessed using 48 cadaveric ACL tissues using immunohistochemistry. The antibody against the transmembrane protein VE-Cadherin was targeted to study the blood vessels. Results: It was observed that the middle part of the ACL was less vascular compared with the peripheral parts of ACL. Conclusion: The knowledge of the ACL vasculature may help in planning surgeries of ACL to reduce postoperative complications.